Cooperation between power plant in East Kalimantan by integrating renewable energy power plant. (May 2019) - Muslimin,; Tambunan, Willy; Wahyuda,
Abstract: Government power plants cannot supply all electricity demand in East Kalimantan Province especially if there is damage to the power plant with the largest production capacity, so cooperation with other suppliers needs to be done. There are four stakeholders that can supply electricity, namely State Electricity Company (SEC), Independent Power Producer (IPP), Rent, and Excess Capacity (EC). Each supplier has different power generation characteristics that lead to differences in fuel costs and emissions. This research proposes 4 mathematical models. The models are scenarios 4 forms of cooperation between electrical stakeholders in East Kalimantan taking into consideration the potential of renewable energy (RE) power plants. This mathematical model is solved with a heuristic algorithm solver excel. The result, the best scenario by integrating three power plants owned by SEC, IPP and RE. Whereas collaboration with the smallest emissions is SEC + Rent + RE.